2011
DOI: 10.1136/tc.2010.038885
|View full text |Cite
|
Sign up to set email alerts
|

Understanding worldwide youth attitudes towards smoke-free policies: an analysis of the Global Youth Tobacco Survey

Abstract: The majority of youth worldwide support, yet lack, smoke-free policies in public places, while being regularly exposed to SHS. Youth support of SFPs is most positively associated with knowledge of the harmful effects of tobacco smoke. Redoubling education efforts represents an opportunity to establish smoke-free environments and improve health of children in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 33 publications
6
47
0
2
Order By: Relevance
“…Even though such laws are a clear public health priority, it is not clear that banning smoking in public places decreases exposure to secondhand smoke equally in all social classes, particularly among children and youth ( Akhtar et al, 2010 ;Sims et al, 2010 ). As far as the support of smoking bans is concerned, a report of the GYTS found that knowledge of harm caused by secondhand smoke was the main variable associated with the support of the laws against smoking in public places ( Koh et al, 2011 ). Raising awareness among teens, especially those attending disadvantaged schools, about the damage caused by secondhand smoke could be useful to increase their support to smoke -free environment legislation.…”
Section: Resultsmentioning
confidence: 99%
“…Even though such laws are a clear public health priority, it is not clear that banning smoking in public places decreases exposure to secondhand smoke equally in all social classes, particularly among children and youth ( Akhtar et al, 2010 ;Sims et al, 2010 ). As far as the support of smoking bans is concerned, a report of the GYTS found that knowledge of harm caused by secondhand smoke was the main variable associated with the support of the laws against smoking in public places ( Koh et al, 2011 ). Raising awareness among teens, especially those attending disadvantaged schools, about the damage caused by secondhand smoke could be useful to increase their support to smoke -free environment legislation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent analysis of the Global Youth Tobacco Survey (2000-06) found that 60.9% of youth from the EMR reported exposure to SHS, compared with 54.2% of youth worldwide [3]. It has been estimated that SHS exposure contributed to the deaths (lower respiratory infections, asthma and otitis media) of some 32 000 children in the EMR in 2004 [4].…”
Section: Introductionmentioning
confidence: 99%
“…The methodology used for weighing, analyzing, and reporting weighted measures has been previously used. 8,16,17 Statistical Analysis Data analysis was performed by SPSS version 20 using complex module to accommodate for sampling weights. Frequencies and proportions were used to describe the variables.…”
Section: Independent Variablesmentioning
confidence: 99%